Sclerostin-Mediated Impaired Osteogenesis by Fibroblast-Like Synoviocytes in the Particle-Induced Osteolysis Model - Jagga, Supriya; Sharma, Ashish Ranjan; Lee, Yeon Hee; Nam, Ju-Suk; Lee, Sang-Soo (Frontiers in Molecular Biosciences, 2021)
Engineered biomaterials are envisioned to replace, augment, or interact with the living tissues for improving the functional deformities associated with end-stage joint pathologies. Unfortunately, wear debris from implant interfaces is the major factor leading to periprosthetic osteolysis. Fibroblast-like synoviocytes (FLS) populate the intimal lining of the synovium and are in direct contact with wear debris. Henceforth, the study was aimed to elucidate the effect of Ti particles as wear debris on human FLS and the mechanism by which it might participate in the bone remodeling process during periprosthetic osteolysis. FLS were isolated from synovial tissue from patients, and condition medium (CM) was collected after treating sterilized Ti particles to FLS. The effect of CM was analyzed for the induction of osteoclastogenesis or any effect on osteogenesis and signaling pathways. Results demonstrated that Ti particles could induce activation of the NFκB signaling pathway and induction of COX-2 and inflammatory cytokines in FLS. The amount of RANKL in conditioned medium (Ti CM) collected from Ti particles stimulated FLS showed the ability to stimulate osteoclast formation. Ti CM also suppressed the osteogenic initial and terminal differentiation markers for osteoprogenitors, like alkaline phosphate activity (ALP), matrix mineralization, collagen synthesis, and expression levels of Osterix, Runx-2, collagen1α, and bone sialoprotein (BSP). Inhibition of the WNT and BMP signaling pathway was observed in the osteoprogenitors after the treatment of Ti CM. In the presence of Ti CM, exogenous stimulation of WNT and BMP signaling pathways failed to stimulate osteogenic activity in osteoprogenitors. Induced expression of sclerostin (SOST: an antagonist of WNT and BMP signaling) in Ti particle treated FLS and secretion of SOST in the Ti CM was detected. Neutralization of SOST in Ti CM partially restored the suppressed WNT and BMP signaling activity as well as the osteogenic activity in osteoprogenitors. Our results reveal that wear debris stimulated FLS might affect bone loss by not only stimulating osteoclastogenesis but also suppressing the bone-forming ability of osteoprogenitors. In the clinical setting, targeting FLS for the secretion of antagonists like SOST might be a novel therapeutic approach for preventing bone loss during inflammatory osteolysis.